Modeling of the dynamic pole-to-pole oscillations of the min proteins in bacterial cell division: The effect of an external field - Charin Modchang (2018)
One of the most important steps in the developmental process of the bacteria cells at the cellular level is the determination of the middle of the cell and the proper placement of the septum, these being essential to the division of the cell. In E. coli, this step depends on the proteins MinC, MinD, and MinE. Exposure to a constant electric field may cause the bacteria's cell-division mechanism to change, resulting in an abnormal cytokinesis. To see the effects of an external field e.g., an electric or magnetic field on this process, we have solved a set of deterministic reaction diffusion equations, which incorporate the influence of an electric field. We have found some changes in the dynamics of the oscillations of the min proteins from pole to pole. The numerical results show some interesting effects, which are qualitatively in good agreement with some experimental results.